2021
DOI: 10.1021/acsami.1c11963
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Effective Thermal Conductivity of Thermal Interface Materials Based on the Genetic Algorithm-Driven Random Thermal Network Model

Abstract: Polymer-based thermal interface materials (TIMs) are indispensable for reducing the thermal contact resistance of high-power electronic devices. Owing to the low thermal conductivity of polymers, adding multiscale dispersed particles with high thermal conductivity is a common approach to enhance the effective thermal conductivity. However, optimizing multiscale particle matching, including particle size distribution and volume fraction, for improving the effective thermal conductivity has not been achieved. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…So, the single h-BN-filled geometric model seems inappropriate for studying the synergistic impact on the overall thermal conductivity . Additionally, some studies have indicated that the effective thermal conductivity of composites closely correlates to the properties of interface because the generated interface thermal resistance affects heat transfer, but the interface components are usually absent for many built finite element models. Therefore, the randomly generated geometric model needs to be further developed, and a comprehensive analysis of the role of the variable is highly desired.…”
Section: Introductionmentioning
confidence: 99%
“…So, the single h-BN-filled geometric model seems inappropriate for studying the synergistic impact on the overall thermal conductivity . Additionally, some studies have indicated that the effective thermal conductivity of composites closely correlates to the properties of interface because the generated interface thermal resistance affects heat transfer, but the interface components are usually absent for many built finite element models. Therefore, the randomly generated geometric model needs to be further developed, and a comprehensive analysis of the role of the variable is highly desired.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of microelectronic techniques, chips are becoming smaller and more integrated, and computing speed is becoming faster. Consequently, a significant amount of heat generates in chips with a small volume, causing the reduction of operating stability and service life. , Heat dissipation has become a critical issue for electronic packing materials. , This problem is usually addressed by the bonding of thermal interface materials (TIMs) between the chips and the heat spreader to transfer the heat generated from the operation of chips, thereby ensuring proper operation of chips. , Polymer materials have been widely applied in the area of TIMs due to their good mechanical properties, electric insulation, convenient durability, and easy processability. However, the thermal conductivities of polymers are not good (about 0.2–0.5 W m K –1 ). To improve the heat conduction performance, thermally conductive fillers are incorporated into the polymer matrix, including BN, AlN, Al 2 O 3 , CNT, and GNP, in which the thermal resistance between fillers is considerable that decreasing the heat conduction efficiency seriously.…”
Section: Introductionmentioning
confidence: 99%
“…For practical applications of TIMs, thermal conductivity is the most intuitive property to exhibit the ability to removal of heat generation by chips. Owing to the low cost and flexibility, polymer-based composites consisting of polymer matrix and thermally conductive fillers have been widely used as TIMs. , With the development of higher power density and larger IC packages, thermal interface materials will be subjected to mechanical stresses strains in the package, resulting in loss of performance . Therefore, thermal interface materials must not only meet the thermal objective but also be stretchable to maintain their performance through the life of the package without significant degradation .…”
Section: Introductionmentioning
confidence: 99%